Deepening Access, Impact, and Adoption of Bundled Digital Farmer Services in Ghana. - Allavi, Elorm; Marcus, Larry; Nunoo, Hannah (2024)
Syecomp’s participation in AICCRA Ghana Cluster activities in 2024 enhanced our resolve to support more farmers beyond our existing farmer client group in Ghana, Togo, Kenya, Uganda, and Rwanda. The project's intervention for 2024 helped over 100,000 smallholder farmers in Ghana to efficiently access agro-advisory services through our platform. Our involvement strengthened our business case to continue building robust, innovative features to tackle emerging challenges in African agriculture. Syecomp’s participation in the AICCRA Ghana Cluster has boosted our engagements with Departments of Agriculture in AICCRA Ghana focus regions, local organisations, and stakeholders to amplify our impact in rural farming communities in Ghana